2014
DOI: 10.1111/pre.12057
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the endangered species Nitellopsis obtusa (Charales, Charophyceae) in western Japan and the genetic differences within and among Japanese populations

Abstract: Summary Nitellopsis obtusa (Charales, Charophyceae) are widely distributed from Europe to Asia; however, this species has been recorded in only the five lakes in central Honshu in Japan. This species was thought to be extinct in Japan, but was rediscovered in limited areas of Lake Kawaguchi in central Honshu. More recently, we discovered more Japanese populations of N. obtusa in Lake Biwa in western Honshu, and it became clear that the species had a broader distribution in Japan than originally believed. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…In Europe, the species has been recorded from Table 3 Species most frequently co-occurring with Nitellopsis obtusa, based on literature sources: (Dąmbska, 1964;Schloesser et al, 1986;Bailly & Schaefer, 2010;Urbaniak & Gąbka, 2014;Styperek et al, 2014;Midwood et al, 2016;Alix et al, 2017;Brainard & Schulz, 2017;Boissezon et al, 2017;Larkin et al, 2018;this (Urbaniak, 2003;Kabus, 2016;Vesić, 2016;Romanov et al, 2018). In Asia, N. obtusa is known from Turkestan, India, Myanmar, China and Japan (Ling et al, 2000;Urbaniak, 2003;Kato et al, 2005Kato et al, , 2014. Although the species is locally red-listed within its native range, it is common in Western, through Central and Eastern European countries.…”
Section: Worldwide Distribution Versus Propagation Mode Of N Obtusamentioning
confidence: 99%
See 2 more Smart Citations
“…In Europe, the species has been recorded from Table 3 Species most frequently co-occurring with Nitellopsis obtusa, based on literature sources: (Dąmbska, 1964;Schloesser et al, 1986;Bailly & Schaefer, 2010;Urbaniak & Gąbka, 2014;Styperek et al, 2014;Midwood et al, 2016;Alix et al, 2017;Brainard & Schulz, 2017;Boissezon et al, 2017;Larkin et al, 2018;this (Urbaniak, 2003;Kabus, 2016;Vesić, 2016;Romanov et al, 2018). In Asia, N. obtusa is known from Turkestan, India, Myanmar, China and Japan (Ling et al, 2000;Urbaniak, 2003;Kato et al, 2005Kato et al, , 2014. Although the species is locally red-listed within its native range, it is common in Western, through Central and Eastern European countries.…”
Section: Worldwide Distribution Versus Propagation Mode Of N Obtusamentioning
confidence: 99%
“…As revised by Larkin et al (2018), the species has been reported from new sites in Europe and its conservations status has locally been lowered. In 2003, N. obtusa was rediscovered in Japan (Kato et al, 2005), after which new populations were found in five lakes, although the species was considered threatened (Kato et al, 2014). The concern was aroused by the fact that the species expanded its range to North America, where for four decades, it has been colonizing new sites bringing the risk of local biodiversity decline (Geist et al, 1981;Escobar et al, 2016;Midwood et al, 2016;Alix et al 2017;Karol & Sleith, 2017).…”
Section: Worldwide Distribution Versus Propagation Mode Of N Obtusamentioning
confidence: 99%
See 1 more Smart Citation
“…Desvaux) J. Groves (starry stonewort) in North America. Nitellopsis obtusa is a dioecious green alga in the Characeae family that is uncommon across much of its native range in Europe and Asia 17 18 and is classified as a priority conservation species in the United Kingdom 19 , near threatened in Switzerland 20 , and endangered in Japan 18 , though there is evidence of expanded distribution in parts of Europe over the past few decades 21 . It occurs in shallow, fresh to brackish water at depths up to 10 m and can reproduce asexually via fragments and star-shaped structures called bulbils 17 .…”
Section: Nitellopsis Obtusa Invasion In North Americamentioning
confidence: 99%
“…Dense growth may also impair recreational activities such as swimming, fishing, and boating [ 1 , 3 ]. Although populations of starry stonewort in their native distribution in Europe and Japan have been declining [ 5 – 7 ], the species has shown great capacity to spread as an aquatic invasive species in North America [ 3 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%